The Effect of Implementing STEAM and 4Dframe Learning in Developing Students’ Computational Thinking Skills - Rio Mardani Suhardi; Gusnandar Yoga Utama (SEAMEO Regional Centre for QITEP in Mathematics, 2022)
Computational thinking skills have been a popular term for teachers worldwide, and PISA 2022 will become the first PISA in evaluating them. Computational thinking helps students enhance their potential in contributing to other disciplines. However, students’ computational thinking skills at SMP Negeri 8 Batam were low. In overcoming the problem, the teacher employed STEAM learning as an alternative approach in stimulating students’ computational thinking skills. A teaching aid, named 4Dframe, was utilised to support the STEAM-based teaching. The objective of this action research study is to illustrate the effect of employing STEAM approach and the 4Dframe as the teaching assistance in developing students' computational thinking skills. The study involved 40 students of 9th grade in SMP Negeri 8 Batam, Indonesia. Three STEAM activities incorporating Warka water tower, Batam-Bintan straw bridge, and planting machine were performed in eight online meetings. In each activity, the students administered decomposition, abstraction, pattern recognition, and algorithm as the cornerstones of computational thinking. The data were gathered through observational forms during the learning and test to evaluate students’ computational thinking skills. The results present that 73% and 88% of students acquired the minimum score for the computational thinking post-tests on the first and second cycle respectively. Although sample and methodology limitations prevent any claim to generalisation, this learning strategy could be implemented as an alternative for conducting mathematics learning activities in elevating students’ computational thinking skills with students in similar contexts.